Evrytime: your fitness trainer / Mohamad Azrie Mohd Azahar - Mohd Azahar, Mohamad Azrie (Faculty of Art and Design, 2020)
Warming up is a preparation for physical exertion or a performance by exercising or practising gently beforehand.